Effect of Salinity Stress on Plant Growth and Yield of Two Varieties of Soybean (Glycine max L.) in Saline Soil - Jeremia Setyo Laksono; Ida Retno Moeljani; Djarwatiningsih Djarwatiningsih (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
This study aims to determine the response of soybean varieties tolerant to salinity stress and the impact of NaCl on the growth and yield of soybean. The study was completely designed randomly with two factors, repeated four times. First factor was NaCl concentration consisting of four levels (0; 2.5; 5; and 7.5 g/l), and second factor was soybean varieties (Wilis and Anjasmoro). The data obtained were analyzed using ANOVA followed by HSD test of 5%. Observation variables included plant height, number of leaves, number of productive branches, number of pods per plant, and weight of 100 seeds. Results showed that both NaCl concentration and soybean variety had no significant effect on plant height, number of pods, and weight of 100 seeds. The interaction of NaCl concentration and variety significantly affected the number of leaves and the number of productive branches. Results showed that Anjasmoro variety with no NaCl (0 g/l) treatment revealed the highest number of leaves, namely 5.50 strands. Whiles, the combination of 7.5 g/l NaCl and Wilis variety produced the highest productive branches, namely 4.25 branches. The results of this study are to provide information on the use of saline land in soybean plants by knowing the resistance of soybean varieties to salinity.